R Factor To Determine The Reynolds Number Of Saturated Water Flowing In Tubes. - Sulaiman, Fauziah; Mahinder Singh, Balbir Singh (2002)

(untitled)
Fluid flowing in a tube is commonly used in practice for heating and cooling applications. The flow in a tube can be laminar or turbulent, entirely depending on the flow conditions. It is therefore, useful to know the nature of the flow, especially in evaluating the Nusselt number.